Predictive values of D-dimer assay, GRACE scores and TIMI scores for adverse outcome in patients with non-ST-segment elevation myocardial infarction - Satilmisoglu MH; Ozyilmaz SO; Gul M; Ak Yildirim H; Kayapinar O; Gokturk K; Aksu H; Erkanli K; Eksik A (Dove Medical Press, 2017)
Muhammet Hulusi Satilmisoglu,1 Sinem Ozbay Ozyilmaz,1 Mehmet Gul,1 Hayriye Ak Yildirim,2 Osman Kayapinar,3 Kadir Gokturk,4 Huseyin Aksu,1 Korhan Erkanli,5 Abdurrahman Eksik1 1Department of Cardiology, 2Department of Biochemistry, Mehmet Akif Ersoy Thoracic and Cardiovascular Surgery Training and Research Hospital, Istanbul, 3Department of Cardiology, Duzce University Faculty of Medicine, Duzce, 4Department of Infectious Diseases, 5Department of Thoracic and Cardiovascular Surgery, Mehmet Akif Ersoy Thoracic and Cardiovascular Surgery Training and Research Hospital, Istanbul, Turkey Purpose: To determine the predictive values of D-dimer assay, Global Registry of Acute Coronary Events (GRACE) and Thrombolysis in Myocardial Infarction (TIMI) risk scores for adverse outcome in patients with non-ST-segment elevation myocardial infarction (NSTEMI).Patients and methods: A total of 234 patients (mean age: 57.2±11.7 years, 75.2% were males) hospitalized with NSTEMI were included. Data on D-dimer assay, GRACE and TIMI risk scores were recorded. Logistic regression analysis was conducted to determine the risk factors predicting increased mortality.Results: Median D-dimer levels were 349.5 (48.0–7,210.0) ng/mL, the average TIMI score was 3.2±1.2 and the GRACE score was 90.4±27.6 with high GRACE scores (>118) in 17.5% of patients. The GRACE score was correlated positively with both the D-dimer assay (r=0.215, P=0.01) and TIMI scores (r=0.504, P=0.000). Multivariate logistic regression analysis revealed that higher creatinine levels (odds ratio =18.465, 95% confidence interval: 1.059–322.084, P=0.046) constituted the only significant predictor of increased mortality risk with no predictive values for age, D-dimer assay, ejection fraction, glucose, hemoglobin A1c, sodium, albumin or total cholesterol levels for mortality.Conclusion: Serum creatinine levels constituted the sole independent determinant of mortality risk, with no significant values for D-dimer assay, GRACE or TIMI scores for predicting the risk of mortality in NSTEMI patients. Keywords: acute coronary syndrome, non-ST-segment elevation myocardial infarction, GRACE score, D-dimer assay, TIMI score